Oxidative stress in a cellular model of alcohol-related liver disease: protection using curcumin nanoformulations - Lucy Petagine; Mohammed G. Zariwala; Satyanarayana Somavarapu; Stefanie Ho Yi Chan; Evrim A. Kaya; Vinood B. Patel (Scientific Reports)
Abstract Alcohol-related liver disease (ARLD) is a global health issue causing significant morbidity and mortality, due to lack of suitable therapeutic options. ARLD induces a spectrum of biochemical and cellular alterations, including chronic oxidative stress, mitochondrial dysfunction, and cell death, resulting in hepatic injury. Natural antioxidant compounds such as curcumin have generated interest in ARLD due to their ability to scavenge reactive oxygen species (ROS), however, therapy using these compounds is limited due to poor bioavailability and stability. Therefore, the aim of this study was to assess the antioxidant potential of free antioxidants and curcumin entrapped formulations against oxidative damage in an ARLD cell model. HepG2 (VL-17A) cells were treated with varying concentrations of alcohol (from 200 to 350 mM) and parameters of oxidative stress and mitochondrial function were assessed over 72 h. Data indicated 350 mM of ethanol led to a significant decrease in cell viability at 72 h, and a significant increase in ROS at 30 min. A substantial number of cells were in late apoptosis at 72 h, and a reduction in the mitochondrial membrane potential was also found. Pre-treatment with curcumin nanoformulations increased viability, as well as, reducing ROS at 2 h, 48 h and 72 h. In summary, antioxidants and entrapped nanoformulations of curcumin were able to ameliorate reduced cell viability and increased ROS caused by ethanol treatment. This demonstrates their potential at mitigating oxidative damage and warrants further investigation to evaluate their efficacy for ARLD therapy.